WATER, SANITATION, AND HYGIENE (WASH) INFRASTRUCTURE AS A DETERMINANT OF INFECTION PREVENTION AND CONTROL (IPC): A FACILITY-BASED CROSS-SECTIONAL STUDY ON COMPLIANCE IN SECONDARY HEALTH FACILITIES IN CONFLICT-AFFECTED SETTINGS IN BORNO STATE, NIGERIA - Usman Balbaya; Adam Ishaku Akyala; Kande Amali; Abah Michael Idoko (INTERNATIONAL JOURNAL OF PUBLIC HEALTH RESEARCH AND DEVELOPMENT, 2026)
In protracted conflict settings, degraded health infrastructure compromises patient safety, yet the dependence of Infection Prevention and Control (IPC) compliance on Water, Sanitation, and Hygiene (WASH) infrastructures is rarely quantified. This study evaluated the relationship between WASH infrastructures and IPC compliance in secondary health facilities in Borno State, Nigeria. A facility-based cross-sectional assessment was conducted in 12 purposively selected secondary health facilities, representing one-third of functional secondary facilities in the state. WASH infrastructures were assessed using the WHO/UNICEF WASH FIT tool and IPC programme maturity using the WHO Infection Prevention and Control Assessment Framework (IPCAF). Pearson correlation and linear regression examined the association between total WASH FIT and IPCAF scores. Findings show that the mean overall WASH FIT score was 50.1% (SD ±30.8), corresponding to a “Basic” service level, with sanitation the weakest domain (41.2%). The mean overall IPCAF score was 40.3% (Basic), with surveillance (Core Component 4, 25.0%) the weakest component. WASH FIT and IPCAF scores were strongly positively correlated (r = 0.842, 95% CI 0.52–0.96, p < 0.001), and WASH infrastructure explained 70.8% of the variance in IPC compliance (R² = 0.708). These indicates that in conflict-affected settings, IPC programme maturity are strongly and significantly associated with the status of underlying WASH infrastructure. Findings thus suggest that infrastructure rehabilitation should be prioritised alongside, and arguably before, IPC training, though the small facility-level sample warrants cautious interpretation and confirmation in larger multi-site studies.